Unexpected Formation of the Highly Symmetric Borate Ion [B(SiCl3)4]−. Issue 26 (24th June 2021) - Bochmann, Sebastian; Böhme, Uwe; Brendler, Erica; Friebel, Mike; Gerwig, Maik; Gründler, Franziska; Günther, Betty; Kroke, Edwin; Lehnert, Robert; Ruppel, Lars
Abstract: Disproportionation reactions of chlorosilane compounds in the presence of boron trichloride yield the compound H[B(SiCl3 )4 ]. Spectroscopic analyses of the yellow‐whitish solid with IR‐, Raman‐, and NMR‐spectroscopy ( 29 Si, 11 B) show the presence of a highly symmetric anion containing boron, which is fourfold coordinated with silicon. Due to the high symmetry 1 J( 11 B, 29 Si) and even 1 J ( 10 B, 29 Si) couplings can be observed in the NMR spectra of the dissolved compound. The crystal structure analysis with a crystal obtained from toluene solution proves the existence of a highly symmetric borate anion, which is stabilized by four trichlorosilyl groups. The molecular structure consists of a para‐protonated toluene cation and the weakly coordinating borate anion [B(SiCl3 )4 ] − . Quantum chemical analysis of the tetrakis(trichlorosilyl)borate ion shows a negatively charged boron atom and the presence of polar Si−Cl and Si−B bonds. Highly reactive compounds [E(SiCl3 )n ] − which are stabilized solely by trichlorosilyl groups have been prepared with E=C, Si, Ge, P, S in recent years. The superacid H[B(SiCl3 )4 ] represents a new member in this elusive compound family. Abstract : Hydrogen tetrakis(trichlorosilyl)borate, H[B(SiCl3 )4 ], was prepared and characterized. The compound shows superacidic properties and features the fluorine‐free weakly coordinating anion [B(SiCl3 )4 ] − as it was shown with the crystal structure of a protonated toluene derivative.